Myricetin Ameliorates Defective Post-Receptor Insulin Signaling via β-Endorphin Signaling in the Skeletal Muscles of Fructose-Fed Rats. (4th June 2011) - Tzeng, Thing-Fong; Liou, Shorong-Shii; Liu, I-Min
Abstract : β -Endorphin plays a major role in the amelioration of insulin resistance. The present study documents that myricetin (3, 5, 7, 3 ′, 4 ′, 5 ′ -hexahydroxyflavone) ameliorates insulin resistance by enhancing β -endorphin production in insulin-resistant rats. The rats were induced for insulin resistance by feeding them a diet containing 60% fructose for 6 weeks. The degree of insulin resistance was measured by the homeostasis model assessment of basal insulin resistance (HOMA-IR). The plasma levels of insulin and β -endorphin were measured by an enzyme-linked immunosorbent assay. The insulin receptor-related signaling mediators in the soleus muscles of rats were evaluated by immunoprecipitation or immunoblotting. Myricetin was injected daily (1 mg kg −1 per injection, thrice daily) for 14 days. Consequently, the high-glucose plasma levels in fructose-fed rats decreased significantly concomitant with an increase in plasma β -endorphin. The reduction of the elevated HOMA-IR index following treatment with myricetin was subsequently inhibited by the administration of β -funaltrexamine hydrochloride ( β -FNA) at doses sufficient to block μ -opioid receptors (MOR). The myricetin treatment was also observed to affect the phosphorylation of the insulin receptor, insulin receptor substrate-1, Akt and Akt substrate of 160 kDa, with subsequent effects on glucose-transporter subtype 4 translocation, all of which were blocked by β -FNA pretreatment. These results indicated that enhancement of β -endorphin secretion, which in turn leads to peripheral MOR activation, is involved in the action of myricetin on the amelioration of impaired signaling intermediates downstream of insulin receptors.